2022
DOI: 10.18805/ag.df-477
|View full text |Cite
|
Sign up to set email alerts
|

​​Levels of Metals and Nutritional Composition of Garden Cress (Lepidium sativum) Seed, in Southern Ethiopia

Abstract: Background: Garden cress (Lepidium sativum) belongs to the Cruciferae family, a fast-growing edible herbaceous plant. This study aimed to determine the essential and non-essential metals levels and nutritional composition of garden cress seed grown in the Wolaita Zone in southern Ethiopia. The study was carried out by collecting garden cress cultivated in Jage, Wandara, Taba, Hilena, Siyara, Demba Gale, Himbecho, Afama and Gara sites of the Wolaita Zone, Southern Ethiopia. Methods: 27 triplicate garden cress s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
1

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 5 publications
0
0
1
Order By: Relevance
“…Analysis of varience showed that the mean concentration of Potasium was significantly different in all sampling sites except Humbo and Damot Woyde. The probable reason due to difference in value may difference in soil nature (Feleke et al, 2023). The level of potasium obtained in this study was lower than the result (382.77 mg/kg) reported by (Saeed et al, 2010).…”
Section: Potassiumcontrasting
confidence: 71%
“…Analysis of varience showed that the mean concentration of Potasium was significantly different in all sampling sites except Humbo and Damot Woyde. The probable reason due to difference in value may difference in soil nature (Feleke et al, 2023). The level of potasium obtained in this study was lower than the result (382.77 mg/kg) reported by (Saeed et al, 2010).…”
Section: Potassiumcontrasting
confidence: 71%